Changing Seasonality of Lolium rigidum (Annual Ryegrass) in Southeastern Australia - Thompson, Michael; Chauhan, Bhagirath Singh (Frontiers in Agronomy, 2022)
Lolium rigidum (annual ryegrass) is the most costly winter weed in Australia and has recently been observed growing in summer. The occurrence of L. rigidum in winter is well documented, but there is no research on populations of this weed that germinate and grow in summer. Herein, we discuss how the potential cause of this seasonal expansion may be related to a change in dormancy duration. Dormancy can affect germination patterns but the growth and reproduction of a plant species depend on other factors, such as temperature and photoperiod. Therefore, dormancy alone cannot be the sole variable responsible for the presence of L. rigidum in summer crops, as typical summer temperature conditions are not favorable for the growth of this weed. Additional changes to the growth and development of summer populations may allow for the adaptation and infestation of L. rigidum in summer conditions.